Spontaneous Ileum Perforation in a premature twin with Coronavirus-19 positive mother - Aminuddin Harahap; Agus Harianto; Risa Etika; Martono Tri Utomo; Dina Angelika; Kartika Darma Handayani; Mahendra Tri Arif Sampurna (Elsevier, 2021)
Spontaneous intestinal perforation (SIP) of the newborn is a single intestinal perforation commonly found in the terminal ileum without distinct causes. These cases often associated with prematurity. The new COVID-19 in pregnancy increased the risk of premature rupture of membranes, preterm delivery, intrauterine fetal death (IUFD), and low birth weight (LBW). Here we report a premature twin with SIP that was born from Coronavirus-19 positive mother.